2019
DOI: 10.1002/asia.201900885
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Template Synthesis of Nanomaterials by Using Microporous Organic Nanoparticles: The Case of C@MoS2 Nanoadsorbents

Abstract: The so‐called colloidal template synthesis has been applied to the preparation of surface‐engineered nanoadsorbents. Colloidal microporous organic network nanotemplates (C‐MONs), which showed a high surface area (611 m2 g−1) and enhanced microporosity, were prepared through the networking of organic building blocks in the presence of poly(vinylpyrrolidone) (PVP). Owing to entrapment of the PVP in networks, the C‐MONs showed good colloidal dispersion in EtOH. MoS2 precursors were incorporated into the C‐MONs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…[51][52][53] ME-MOPs can be utilized as platforms for the synthesis of new functional materials. [54][55][56][57][58] For example, through the incorporation of various precursors into ME-MOPs, new inorganic and composite materials could be synthesized. Moreover, ME-MOPs can extend the application elds of MOPs.…”
Section: Benefits Of Me-mopsmentioning
confidence: 99%
See 1 more Smart Citation
“…[51][52][53] ME-MOPs can be utilized as platforms for the synthesis of new functional materials. [54][55][56][57][58] For example, through the incorporation of various precursors into ME-MOPs, new inorganic and composite materials could be synthesized. Moreover, ME-MOPs can extend the application elds of MOPs.…”
Section: Benefits Of Me-mopsmentioning
confidence: 99%
“…[51][52][53] ME-MOPs can be utilized as platform materials for the synthesis of new functional inorganic and nanocomposite materials. [54][55][56][57][58] Moreover, ME-MOPs can open new application elds. [59][60][61][62][63][64][65][66] Whilst there have been recent reviews on the synthesis and application of MOPs, [1][2][3][4][5][6][7][8]20 this review article focuses on the synthetic methods for ME-MOPs as well as the benets provided over conventional MOPs.…”
Section: Introductionmentioning
confidence: 99%
“…In the carbonaceous MoS 2 materials, the carbon acts as an electronic conductive supporting material preventing agglomeration of MoS 2 . The carbonaceous MoS 2 materials have been synthesized via nano‐structuring, hydrothermal reaction or hybridization approaches . Recent studies reported that doping of heteroatoms such as B, N, O, P and S in carbon gives rise to electrode performance of the carbon in SIBs because of a favorable change in adsorption energy of sodium ions upon the heteroatom‐doping .…”
Section: Figurementioning
confidence: 99%
“…[10,11] The carbonaceous MoS 2 materials have been synthesized via nano-structuring, hydrothermal reaction or hybridization approaches. [12][13][14] Recent studies reported that doping of heteroatoms such as B, N, O, P and S in carbon gives rise to electrode performance of the carbon in SIBs because of a favorable change in adsorption energy of sodium ions upon the heteroatom-doping. [15][16][17] In general, synthetic routes for the multicomponent materials are more complex and challenging when the number of component elements is increased.…”
mentioning
confidence: 99%
“…[19][20][21][22][23][24] The surfactant templating approach has been considered an attractive method to create nanostructured materials. [25][26][27] As opposed to hard templates, soft templates offer advantages in terms of scaling and cost effectiveness. Surfactants or amphiphilic molecules are of particular interest because they can be assembled into various forms, such as spheres, cylinders, and lamella, depending on their molecular structure and concentration.…”
mentioning
confidence: 99%